Assessing cancer knowledge among pharmacy students in Jordan: Bridging the gap between theory and practice - Ali Hmedat; Haneen Amawi; Ghaith Al-Taani (PLoS ONE, 2025)
Background Early detection of cancer is essential in improving patients’ clinical outcomes. As future first-line health providers, pharmacy students must possess strong knowledge and education regarding cancer risk factors, early signs and symptoms, and available screening methods. The current study aimed to assess knowledge among pharmacy students at various Jordanian universities concerning key cancer related topics. This study particularly assessed the students’ knowledge and awareness of cancer signs and symptoms, associated risk factors, and possible screening methods. Methods This cross-sectional study was conducted from June to September 2024, using an online survey among pharmacy students from various Jordanian schools to assess their knowledge about cancer and its warning signs, risk factors and screening recommendations. The questionnaire was distributed electronically through student networks and in collaboration with pharmacy schools across Jordan. Participation was voluntary, and students were included based on their consent to participate. Data analysis was performed using the Statistical Package for Social Sciences (SPSS) version 26. Bivariate correlations were assessed using Spearman’s rank correlation. Additionally, simple, multiple, and backward linear regression analyses were conducted to identify significant predictors of cancer knowledge. Results More than 60% of pharmacy students considered cancer education adequate in their programs. However, around half reported insufficient knowledge about the management of cancer patients and safe handling of anticancer medicines. Few of respondents correctly identified warning signs of cancer, with the mean summated score of 6.1 out of the maximum possible 12. The mean summated score equaled 7.8 out of 14 maximum possible scores about cancer risk factors. Linear regression analyses showed that students without a personal history of cancer and those who believe it is important to have oral chemotherapy knowledge have increased knowledge about cancer related topics. Also, those interested in continuing education programs on oral chemotherapy have higher knowledge about cancer warning signs. Conclusion The results revealed gaps in practical cancer education and the knowledge in cancer risk factors and warning signs among pharmacy students. Thus, enhanced oncology education is essential to better prepare pharmacy students to contribute effectively to multidisciplinary cancer care teams.